Comparative Analysis of The Cost of Laying Red Bricks on Building Works : Case Study: Cigarette Depot Building PT. Gudang Garam Tbk - Reza Mulyanto; Yudi Setio Prabowo (CV. Publikasi Indonesia, 2024)
Technological development continues to fulfill people's needs for work comfort. A non-structural work that has an important role in building construction projects, such as labor productivity of red brick wall installation work. This research was conducted to analyze the comparison of the average labor coefficient and labor requirements in the field with SNI 2022, as well as comparing labor wages in the field with SSHBJ. This research was conducted by conducting unstructured interviews with the site manager, to obtain primary data on the construction project of the PT Gudang Garam Tbk, cigarette depot building. This research uses quantitative methods. From the results of this analysis, the average value of the foreman's labor coefficient in the field is 0.0141: 1.0150 OH SNI, head mason in the field 0.0205: 0.0100 OH SNI, mason in the field 0.0100: 0.0100 OH SNI, helper mason in the field 0.1215: 0.3000 OH SNI. The following are the results of the comparison of the average labor requirements of foremen in the field 1: 1 OH SNI, head masons in the field 2: 1 OH SNI, mason in the field 10: 9 OH SNI, mason helper in the field 11: 28 OH SNI. Where the average wage of labor in the field is compared with SSHBJ, where for the foreman's labor in the field Rp 288,066.67: 178,500.00 SSHBJ, head mason in the field Rp 141,646.15: 245,323.08 SSHBJ, masons in the field Rp 1,635,361.54:1,260,000.00 SSHBJ, mason helper Rp 4,359,871.79: 1.120.512,82 SSHBJ.